Adolescents' Knowledge And Attitudes Towards Bullying - Fernando, Muhamad Herman; Ulum, Mochamad Miftahul; Rachmawati, Dewi (Poltekkes Kemenkes Malang, Campus III Blitar, 2024)
Bullying in adolescents is one of the things that can cause negative impacts. Until March 31, 2023 KPAI received 64 complaints of violence at the education level. This study aims to identify adolescents' knowledge and attitudes towards bullying at MTSN 1 Blitar in 2023/2024. The research design used is descriptive. Simple random sampling technique with a sampling of 78 respondents. This research data was collected in February 2024 with questionnaires distributed in the classroom. The results showed that most adolescents had good knowledge 95% (76 people) of 78 respondents because the school implemented Islamic religious learning and counseling learning carried out by the school and most had a positive attitude as much as 83% (65 people) because students applied the results of knowing and understanding of bullying. It is hoped that this research can be used to increase knowledge about bullying behavior and attitudes towards bullying and can be used as input for schools to continue to improve learning and counseling services for adolescent development.